E Efektivitas Penggunaan Media Pembelajaran Berbasis Wordwall dalam Pembelajaran Matematika Pada Siswa Kelas V SDN 193 Mandalan: Penelitian Kuantitatif - Binti Bahri, Nur Afni; Baharullah; Mutmainnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem in this study is the effectiveness of using wordwall media in learning, especially for fifth grade students at SDN 193 Mandalan. The purpose of this study was to determine the effectiveness of mathematics learning outcomes using wordwall-based learning media for fifth grade students at SDN 193 Mandalan. The method used was experimental research with a pre-experimental design approach, specifically the one-group pretest-posttest design model. The subjects in this study were all fifth grade students at SDN 193 Mandalan, totaling 12 students. Data were collected through learning outcome tests (pretest and posttest), student activity observation sheets, and student response questionnaires on the use of learning media. The results of this study indicate that the data were analyzed using descriptive and inferential analysis approaches. Through descriptive analysis, the average pretest value was 51.66, while the average posttest value reached 81.66. The average posttest value was higher than the pretest. In addition, the average percentage of student activity in using the number board media was 94.41%, which showed a positive response and was categorized as very good, while 18.04% gave a negative response which was categorized as sufficient. The average percentage of student questionnaire responses to the use of wordwall media was recorded at 90.08%, which was categorized as good (positive). Based on inferential statistical analysis, the t-count value was 9.950 with degrees of freedom (df) = 11, at a significance level of 0.05, and the t-table value was 2.201. Because t-count > t-table, H0 is rejected and H1 is accepted. Based on these findings, it can be concluded that the use of wordwall-based learning media is effective in increasing knowledge of the material on quadrilaterals in grade V students of SDN 193 Mandalan.